Monitoring of power transformers using thermal model and permission time of overload - Huthaifa Ahmad Al_Issa; Mohamed Qawaqzeh; Serhii Kurashkin; Serhii Halko; Serhii Kvitka; Oleksandr Vovk; Oleksandr Miroshnyk (Institute of Advanced Engineering and Science, 2022)
This paper presents the problem of increasing the reliability of electricity supply to consumers. Uninterrupted power supply to electricity consumers depends on the reliability of power supply system in general and power transformers in particular, the accident rate of which is quite high. The causes of the problem are the location of transformer substations at a considerable distance from the service centers, their spreading out over a large area, missing information about the current modes of their operation and so on. One of the ways to solve this problem is development and implementation a system for continuous diagnostics of power transformers. Failure analysis of power transformer based on fault tree is considered, the diagnostic parameters are determined. The insulation wear rate and permission operating time under overload have been defined with help of equivalent heat circuit. It is proposed to use a permission time as a parameter to diagnose the operation mode and increase the efficiency of maintenance of substations through remote monitoring based on the global service mobile (GSM) network. Remote diagnostics allows to receive an information about emergency situation timely. It helps to reduce operating costs, to ensure the reliability and quality of electricity supply for consumers.